Protein Quality of Legume-Based Milk Pudding as an Alternative Snack for Malnourished Toddlers - Mir'ah Firdausi; Utami Harjantini; Muhana Rafika; Husnul Khatimah (Universitas Islam Negeri Walisongo Semarang, 2025)
Malnutrition in early childhood can hinder children’s development and their potential in their upcoming productive ages. The prevalence of wasting among children under five in Indonesia was 7.4% in 2025. This study developed a complementary feeding product in the form of milk pudding with the addition of mung beans, soybeans, and red beans. The study aimed to analyze the protein content, protein digestibility, and acceptability of the legume-based milk pudding. A completely randomized design (CRD) was used, consisting of treatment groups with the addition of mung beans, soybeans, and red beans (F1, F2, F3) and a control group (FK). Each treatment group was replicated twice, resulting in a total of eight experimental units. The results showed that pudding F2, with the addition of 120 g mung beans, 60 g soybeans, and 120 g red beans, had the highest total protein content (2.80%) and a protein digestibility value of 61.86%. There was a significant difference among groups in total protein content (P = 0.002), but no significant difference in protein digestibility (P = 0.834). The highest acceptance value was found in pudding F3, with color, aroma, texture, and taste scores ranging from 3.13 to 3.80. There were no differences among groups in aroma, taste, and texture (P > 0.05), whereas color showed significant differences among treatment groups (P = 0.001). Milk pudding with mung beans, soybeans, and red beans can serve as an alternative local snack food, contributing approximately 12.25% to the daily protein requirements of toddlers.